THE USE OF SPELLING BEE GAMES IN IMPROVING ENGLISH VOCABULARY STUDENTS AT NEGERI 8 MAKASSAR - NATALIA PADIDI; DAHLIA D. MOELIER; A HAMZAH FANSURY (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2022)
This research was conducted with the aim of determining whether or not there was an improving in students' English vocabulary by using Spelling bee games in grade 7 students of SMP Negeri 8 Makassar. This study used a pre-experimental design with pre-test, post-test, and data analysis.The population in this study were students of SMP Negeri 8 Makassar for the 2021/2022 school year. the sample in this study was 36 students in grade 7.4. The results of this study were analyzed using a paired sample T-test on SPSS. According to the results of using the bee spelling game, it can increase the vocabulary of grade 7.4 students of SMP Negeri 8 Makassar.This can be seen based on the results of the Paired Sample T-test on the pre-test value the column is 0.00. Thus, it can be concluded that the Spelling Bee games can improve students' vocabulary skills in english learning at SMP Negeri 8 Makassar. Key Words: Spelling Bee, Games, Vocabulary